The Role of Appendectomy in the Regulating of Immune Function - Al-Shibli, Nasib (European Journal of Applied Sciences, 2023)
The removal of the little organ known as the vermiform appendix, which is situated in the lower right abdomen, is a routine surgical surgery known as an appendectomy. Despite being historically regarded as a non-essential organ, new research indicates that the appendix may be crucial in the control of the immune system. This review article examines the evidence for the role of appendectomy in modulating immune function, with a focus on its effects on inflammation and autoimmunity, and summarizes recent research on the subject. It also discusses potential implications for clinical practice. Appendectomy may affect immune system functioning, including changes in lymphocyte populations, cytokine production, and antibody responses, according to results of research conducted on both animals and humans. These results imply that appendectomy could have an effect on immune system regulation and should be considered when assessing patients with immunological disorders. To evaluate if these effects are clinically relevant and to better understand the processes that underlie them, more study is required.